Prophylactic norepinephrine infusion to treat hypotension after spinal anaesthesia during caesarean section: a meta-analysis - Chunli Zhang; Jie Qiu; Yuyuan Huang; Renkang Tan (Journal of Obstetrics and Gynaecology)
Background Spinal anaesthesia is a common anaesthetic method for caesarean sections but often results in hypotension, posing potential risks to maternal and neonatal health. Norepinephrine, as a vasopressor, may be effective in preventing and treating this hypotension. This systematic review and meta-analysis aims to systematically evaluate the efficacy and safety of prophylactic norepinephrine infusion for the treatment of hypotension following spinal anaesthesia in caesarean sections.Methods Literature searches were conducted in PubMed, Embase, Web of Science, Cochrane Library, CNKI, Wanfang, and VIP databases for relevant studies on prophylactic administration of norepinephrine for the treatment of hypotension after spinal anaesthesia in caesarean delivery. Reference lists of included articles were also searched. The latest search update was on March 20, 2024. Meta-analysis was conducted using R software. The methods recommended by the Cochrane Handbook, Begge’s and Egger’s tests were used for risk of bias evaluation of the included literature.Results Nine studies were finally included in this study. The results showed that prophylactic administration of norepinephrine was superior to the control group in four aspects of treating hypotension after spinal anaesthesia in caesarean delivery: the incidence of hypotension was reduced [RR = 0.34, 95%CI (0.27–0.43), P < 0.01]; the incidence of severe hypotension was reduced [RR = 0.32, 95%CI (0.21–0.51), P < 0.01]; and maternal blood pressure was more stable with MDPE [MD = –5.00, 95%CI (–7.80–−2.21), P = 0.06] and MDAPE [MD = 4.11, 95%CI (1.38–6.85), P < 0.05], the incidence of nausea and vomiting was reduced [RR = 0.52, 95%CI (0.35–0.77), P < 0.01]. On the other hand, the incidence of reactive hypertension was higher than the control group [RR = 3.58, 95%CI (1.94–6.58), P < 0.01]. There was no difference between the two groups in one aspects: newborn Apgar scores [MD = –0.01, 95%CI (–0.10–0.09, P = 0.85)].Conclusion Prophylactic administration of norepinephrine is effective in treating hypotension after spinal anaesthesia in caesarean delivery patients; however, it does not provide improved safety and carries a risk of inducing reactive hypertension.